Can direct oral anticoagulants be used in kidney transplant recipients?. Issue 12 (23rd September 2021) - Parker, Kathrine; Chu, Janette; Morton, Muir; Bhutani, Shiv; Picton, Michael; Mitra, Sandip; Thachil, Jecko
Abstract: Background: : Kidney transplant recipients(KTRs) are at an increased risk of venous thromboembolism (VTE) and atrial fibrillation(AF). Direct oral anticoagulants (DOACs) have shown important advantages over vitamin K antagonists; however, in KTRs, concerns regarding interactions and use in severe kidney disease may limit their use. This evaluation describes a large UK kidney transplant center's experience of DOACs in KTRs with CrCl > 15 mL/min. Methods: Electronic records were reviewed for all adult KTRs at Manchester University Foundation Trust Hospitals taking DOACs between January 2018 and October 2020 with VTE or AF. The primary outcome was trough and peak DOAC levels within the expected reference ranges and secondary outcomes included bleeding and thrombotic events. Results: In 31 KTRs taking DOACS, eight patients had a CrCl < 30 mL/min. Overall, 94% (62/66) of DOAC levels were within the recommended ranges. There were no thrombotic events and four bleeding events (two major and two clinically relevant non‐major bleeds). The overall bleeding rate was 6.9 per 100 patient‐years at risk. Conclusions: There was no evidence of a significant interaction of apixaban or rivaroxaban with CNIs based on expected DOAC and CNI levels. Their use was found to be safe and effective with no VTE events and bleeding episodes similar to published trial data.